Utilization of coconut water waste to increase cocoa growth seedling by different application methods and intervals. Issue 1 (February 2021) - Rosniawaty, S; Ariyanti, M; Suherman, C; Sudirja, R; Fitria, S
Abstract: Giving coconut water might increase cocoa seedling growth because coconut water contains nutrients and hormone that is needed for plant growth. This experiment was conducted to study the growth response of cocoa seedlings towards the application of coconut water. The experiment was conducted from October 2019 until February 2020 in Ciparanje field station, Padjadjaran University, Jatinangor with the altitude of 760 meter above the sea level. Experimental design used was randomized block design (RBD) with nine treatments and each treatment was repeated three times. The treatments consisted of control application (urea 2 g every 12 days), coconut water application towards plant every 3, 7, 14, 21 days, and to the soil every 3, 7, 14, 21 days. The application of coconut water every 21 days to the plant and to the soil affected the seedling height at 12 WAA (week after application) and on the stem diameter in 8 WAA. Negligible differences were observed between application method and intervals with leaf number and chlorophyll index of seedlings.